EDUKASI KORESPONDENSI UNTUK PESERTA DIDIK DI SMKN 8 KOTA SERANG: CORRESPONDENCE TRAINING FOR STUDENTS OF SMKN 8 SERANG CITY - Thea Umbarasari (Jurnal Dedikasi Matematika & Sains, 2025)
Community Service Program (PkM) entitled “Correspondence Education For Students Of State Vocational High School 8 In Serang City” was conducted to address students’ low ability in writing formal letters according to correspondence rules. The main problems faced by the students include low interest in writing, the use of informal language, and the lack of accuracy in structuring letters. The purpose of this program was to provide knowledge and practical skills in correspondence, particularly in writing formal letters, so that students would be better prepared for the professional world. The implementation method included initial observation, preparation of training materials, interactive lectures, small group mentoring, and evaluation of students’ writing products. The program was carried out using both individual and classical approaches with a participatory learning method. The results showed a significant improvement in students’ comprehension and writing skills. Before the training, most students were categorized as “fair” (37.5%), while after the training the majority improved to the “very good” category (47.5%). This indicates that interactive teaching combined with direct practice and reflection is effective in enhancing vocational high school students’ correspondence skills. This program is expected to serve as a foundation for sustainable literacy development in partner schools and strengthen collaboration between universities and vocational high schools.